2015
DOI: 10.3390/ijms16011526
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Expression of Onco-Related miRNAs and the Endoscopic Appearance of Colorectal Tumors

Abstract: Accumulating data indicates that certain microRNAs (miRNAs or miRs) are differently expressed in samples of tumors and paired non-tumorous samples taken from the same patients with colorectal tumors. We examined the expression of onco-related miRNAs in 131 sporadic exophytic adenomas or early cancers and in 52 sporadic flat elevated adenomas or early cancers to clarify the relationship between the expression of the miRNAs and the endoscopic morphological appearance of the colorectal tumors. The expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Another group showed that miR-7 was gradually increasingly overexpressed with each subsequent step of carcinogenesis, from low-grade dysplasia to advanced CRC. Moreover, the transfection of human colon cancer DLD-1 cells with anti-miR-7 suppressed proliferation, suggesting that miR-7 might function as an oncogenic role in CRC (14). Consistent with these findings, our current study also demonstrated that miR-7 expression levels were higher in CRC tissues compared with normal mucosae, especially in advanced cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another group showed that miR-7 was gradually increasingly overexpressed with each subsequent step of carcinogenesis, from low-grade dysplasia to advanced CRC. Moreover, the transfection of human colon cancer DLD-1 cells with anti-miR-7 suppressed proliferation, suggesting that miR-7 might function as an oncogenic role in CRC (14). Consistent with these findings, our current study also demonstrated that miR-7 expression levels were higher in CRC tissues compared with normal mucosae, especially in advanced cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies characterised miR-7 as a tumour-suppressor gene in several types of cancer, including melanoma (11) and breast cancer (12). In those studies, miR-7 was shown to reduce the expression of several oncogenes, such as epidermal growth factor receptor (14), p21-activated kinase 1 (15), and others (16).…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer (CRC), miR-7 was found to be upregulated in advanced cancers and in selected cell lines (SW480, DLD-1, and COLO201) compared to normal mucosa. In addition, transfection with anti-miR-7 was shown to suppress cell growth in DLD-1 and COLO201 [ 67 ]. miR-7 was also reported to be increased in the stool of CRC patients, giving rise to the notion of a screening method for CRC [ 68 ].…”
Section: The Role Of Microrna-7 In Cancermentioning
confidence: 99%
“…The percentage of gene mutation in the protruded tumor is hypothesized to be different from that of the LST [13] . When we focused on miRNA, expression changes of some miRNAs in exophytic and flat elevated tumors were reported [14] ; however, there is no analysis comparing miRNA expressions of the LST with those of the protruded tumor.…”
Section: Introductionmentioning
confidence: 99%